ANALISIS FAKTOR EKONOMI DAN NON EKONOMI YANG MEMPENGARUHI PERILAKU KONSUMEN INDOMARET (STUDI KASUS INDOMARET DESA RUMAH TIGA KOTA AMBON) - Stenly Manuhutu; Desry Jonelda Louhenapessy; Izaac Tonny Matitaputty (Jurnal Cita Ekonomika, 2021)
The purpose of this research is: 1) To find out the influence of economic factors on the behavior of indomaret consumers in Rumah Tiga Village of Ambon City. 2) To find out the influence of non-economic factors on the behavior of indomaret consumers in Rumah Tiga Village of Ambon City 3) Provide references for student friends to find out the influence of Economic and Non-Economic Factors on Indomaret Consumer Behavior in Rumah Tiga Village of Ambon City to be developed in future research The result of study show that economic (X1) and non economic (X2) variables have a significant influence on the Y variable (consumer behavior). This can be seen from the F test result, so F count > F table (20.441 > 3.16) or sig F < 5% (0.000< 0.05). The economic factor that most influences the dependent variable is consumer behavior. This is based on the result of the t-test X1 where t count > t table (4.296 > 2.0024) or the significance of t < 5% (0.000< 0.05) then partially X1 variable (economic factor) has a significant influence on the Y variable (consumer behavior).